Efforts To Improve Biology Learning Through Media Picture Of Student Class Xi Sma Negeri 6 Padang Lesson 2014-2015 - Deswaniar Deswaniar (Jurnal Ilmiah Pendidikan Scholastic, 2018)
In learning to learn something well, we need to use our existing senses such as listening, seeing, and asking questions about material discussions with teachers or others. Not only that, teachers need to "teach it", that is to describe something in their own way, for example, trying to practice skills and doing tasks that demand knowledge they have gained. The problems studied in this research are: a) How to improve biology learning outcomes by applying the model of learning with the media images in class XI SMA N 6 Padang? B) The steps taken in improving the biology learning achievement in grade XI SMA N 6 Padang. Place of improvement of learning SMA N 6 Padang Class: XI Number of students 29. Biology Subject, Time of Implementation January 3, 2015: Implementation of Cycle I January 14, 2015: Implementation of Cycle II. Procedure PTK Improvement of learning carried out in the process of the cycle consists of 4 stages: Melalukan planning (planning) Acting, Observation (Observation) Reflection. The results of the reflection in the ppenulis made in the guidelines to make further improvements, if the actions taken are considered successful, the improvement can be carried out several times until the learning is achieved well and the results are increased and satisfactory value. From the results of learning that has been carried out clearly that the use of appropriate media and the use of various methods can improve students' understanding of learning materials about human respiratory equipment in students of class XI SMA N. 6 Padang. Based on the learning that has been done in obtaining the following results: 1) Obtaining pre-cycle value of 25.9%. This is caused by using image media 2) Obtaining the value of cycle I, that is equal to 59.26%. This is caused by the use of image media and using varied methods 3) Acquisition cycle II, which is equal to 96.3%. This is caused in the given material by using the image media. Based on the acquisition value that always increases trsebut, can be concluded that, the media images improve student learning outcomes.